SOURCES WITH LOW-FREQUENCY STEEPNESS SPECTRUM CONCERNING THE UNIFIED MODEL - Miroshnichenko, A. P. (Одеські астрономічні публікації, 2012)
Based on data of the data of the Grakovo catalogue of the extragalactic sources, detected at the decametre band with the UTR-2 radio telescope , it was established, that properties of radio sources with lowfrequency steepness of spectrum are in accordance with the long evolution. At that, quasars and galaxies with lowfrequency steep spectra often are the sources of the infrared and the X-ray radiation. In the last case we use the possibility of alternative determination of the magnetic field strength in the sources necessary for the estimate of the ratio of the magnetic field energy and the energy of the relativistic particles. Also we obtained the relations of sources luminosities at the radio, infrared, optical, X-ray bands that revealed evolution effects. The analysis of considered relations for quasars and galaxies with lowfrequency steepness of radio spectrum testifies for the unified model of sources.